2013
DOI: 10.1007/s00429-013-0655-y
|View full text |Cite
|
Sign up to set email alerts
|

Optic radiation structure and anatomy in the normally developing brain determined using diffusion MRI and tractography

Abstract: The optic radiation (OR) is a component of the visual system known to be myelin mature very early in life. Diffusion tensor imaging (DTI) and its unique ability to reconstruct the OR in vivo were used to study structural maturation through analysis of DTI metrics in a cohort of 90 children aged 5–18 years. As the OR is at risk of damage during epilepsy surgery, we measured its position relative to characteristic anatomical landmarks. Anatomical distances, DTI metrics and volume of the OR were investigated for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
35
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 41 publications
(41 citation statements)
references
References 93 publications
6
35
0
Order By: Relevance
“…Our findings are consistent with a prior study of children and youth that found left lateralization of FA values due to a higher first eigenvalue, suggesting a lower axon density in the left hemisphere (Dayan et al, 2015). As myelination of the optic radiation is mature by three years of age (Brown et al, 2014), a two- to three-year longitudinal follow-up of our cohort is needed to investigate changes in diffusion measures over the latter phase of maturation.…”
Section: Discussionsupporting
confidence: 93%
“…Our findings are consistent with a prior study of children and youth that found left lateralization of FA values due to a higher first eigenvalue, suggesting a lower axon density in the left hemisphere (Dayan et al, 2015). As myelination of the optic radiation is mature by three years of age (Brown et al, 2014), a two- to three-year longitudinal follow-up of our cohort is needed to investigate changes in diffusion measures over the latter phase of maturation.…”
Section: Discussionsupporting
confidence: 93%
“…This may be the result of a number of differences in the microstructural characteristics, including smaller axon diameter, denser axonal packing, or higher myelination [Le Bihan, ; Pierpaoli and Basser, ]. There is evidence for left‐ and/or rightward asymmetries in varying combinations of FA, AD, MD, and RD in the optic radiations of healthy participants, yet to our knowledge, previous research has not accounted for any differences dependent on eye dominance [Dayan et al, ; de Schotten et al, ; Sherbondy et al, ]. Ocular dominance is shown to influence functional activity in V1 such that the proportion of activation is considerably greater when the dominant eye is stimulated compared to the nondominant eye [Menon et al, ; Rombouts et al, ].…”
Section: Discussionmentioning
confidence: 99%
“…The position of the most anterior voxel belonging to the OR was chosen as the location of the tip of ML. The location of the temporal pole (TP) was evaluated on the color‐coded FA maps and chosen as the coronal slice coinciding with the most anterior extent of the temporal lobe – including the TP – and the beginning of the frontal lobe . In cases where several coronal plane positions along the anterior–posterior axis fit this criterion, the most anterior position was systematically selected.…”
Section: Methodsmentioning
confidence: 99%